Bringing Mindfulness to the K-6 Classroom (LEARNing Landscapes, 2017)
In this interview, elementary school teacher and mindfulness coach Barbara Kurtzman discusses how she brought mindfulness in the class, starting in Cycle 1 and then with the whole elementary school. Her interest in mindfulness began as a personal journey which she wanted to share with her students. She explains that taking only a few minutes a day helps her and her students to be more focused on the task at hand. She has found that her students also use mindfulness outside of her classroom. She finishes by giving advice to teachers who are interested in including mindfulness in their classrooms.
Keywords: mindfulness; k-6; elementary school; teacher; focus